The Association between Sickle Cell Disease and Postpartum Severe Maternal Morbidity - Poliektov, Natalie E.; Vuncannon, Danielle M.; Ha, Thoa K.; Lindsay, Michael K.; Chandrasekaran, Suchitra (American Journal of Perinatology, 2024)
Objective To compare the risk of severe maternal morbidity (SMM) from the delivery admission to 42 days' postdischarge among persons with sickle cell disease (SCD) to those without SCD.Study Design This retrospective cohort study included deliveries ≥20 weeks' gestation at an urban safety net hospital in Atlanta, GA from 2011 to 2019. The exposure was SCD diagnosis. The outcome was a composite of SMM from the delivery admission to 42 days' postdischarge. SMM indicators as defined by the Centers for Disease Control and Prevention were identified using the International Classification of Diseases, Ninth and Tenth Revisions (ICD-9/10) codes; transfusion of blood products and sickle cell crisis were excluded.Results Of N = 17,354 delivery admissions, n = 92 (0.53%) had SCD. Persons with SCD versus without SCD had an increased risk of composite SMM (15.22 vs. 2.29%, p < 0.001), acute renal failure (6.52 vs. 0.71%, p < 0.001), acute respiratory distress syndrome (4.35 vs. 0.17%, p < 0.001), puerperal cerebrovascular disorders (3.26 vs. 0.10%, p < 0.001), sepsis (4.35 vs. 0.42%, p < 0.01), air and thrombotic embolism (5.43 vs. 0.10%, p < 0.001), and ventilation (2.17 vs. 0.09%, p < 0.01). Ultimately, those with SCD had an approximately 6-fold higher incidence risk ratio of SMM, which remained after adjustment for confounders (adjusted incidence risk ratio [aIRR]: 5.96, 95% confidence interval [CI]: 3.4–9.19, p < 0.001). Persons with SCD in active vaso-occlusive crisis at the delivery admission had an approximately 9-fold higher risk of SMM up to 42 days' postdischarge compared with those with SCD not in crisis at the delivery admission (incidence: 25.71 vs. 8.77%, p < 0.05; aIRR: 8.92, 95% CI: 4.5–10.04, p < 0.05). Among those with SCD, SMM at the delivery admission was primarily related to renal and cerebrovascular events, whereas most postpartum SMM was related to respiratory events or sepsis.Conclusion SCD is significantly associated with an increased risk of SMM during the delivery admission and through 42 days' postdischarge. Active crisis at delivery further increases the risk of SMM.Key Points
Keywords: sickle cell disease; sickle cell crisis; severe maternal morbidity; composite maternal morbidity; pregnancy; delivery; postpartum